PENGEMBANGAN MATERI SIKAP BULLYING REMAJA UNTUK SISWA SMA/SEDERAJAT - Rosa Mutiqa; Zulfan Saam; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: One of the problems that occur on adolescents at school is bullying.Bullying is something that should not occur due to the fact that one of bullying impacts is thedecreasing of students’ achievement at school and caused bad relationship in friendship.Therefore, its necessary to develop material services to be the material on Adolescentbullying behavior, and it sis expected to be applied by guidance and counseling teachers to beshared to their students. The objectives of this research are (1) to arrange the material onadolescent bullying behavior based on the clarity, the systematic, the supporting pictures, theinstruments, the novelty of material, and the supporting of game and video, (2) to know thematerial quality of adolescent bullying behavior. The material is arranged by using researchand development method, then it is experimented to the students with the time allocated is 4lesson hours (4 x 45’). This material is validated by first and second guidance lectures,guidance and counseling teachers,and the students of SMA 2 Pekanbaru. The materialsconsist of definition of bullying, adolescent time, the factors that influence bullying, thecomponents and the characteristics of bullying, the place where bullying take place, thenegative impact of bullying, and the strategies to inhibit bullying. The result of the materialdevelopment is the arrangement a self-adjustment module with the material quality is in“Very Good” category with the score obtained 4.34 for the whole aspects of assessment.Keywords: Guidance and counseling, Bullying behavior, Senior High School